2020
DOI: 10.5897/jen2019.0240
|View full text |Cite
|
Sign up to set email alerts
|

Infestation rate of Mangifera indica fruit fly in Sudanese zone of Mali

Abstract: Mali has a potential for mango production across the country. However, this plant is facing phytosanitary problems mainly related to fruit flies. The study was conducted to evaluate the infestation rate of fruit flies on mango varieties in Sudanese zone of Mali (Kati). Stung mangoes were weekly collected from three sites. Fruits were weighted and placed inside plastic bags containing sand to the monitor larva infestation under semi-natural conditions within of the laboratory. Bactrocera dorsalis and Ceratitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The shade of grown trees can also protect against excessive sun exposure and create the ideal temperature and humidity for fruit flies. Rahinatou et al (2020) suggested that the temperature and humidity play a role in fruit fly populations, when the temperature drops (below 30°) in increasing humidity (greater than 70%), the population of C. cosyra decreases, whereas B. dorsalis increases. Meanwhile, according to Raghuvanshi et al (2012), the temperature played a specific role in regulating the behavior of the fruit fly adults, which indicates the positive correlation of prevailing temperature with the number of ovipositing females; thus, the influence of relative humidity and rainfall harmed female abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The shade of grown trees can also protect against excessive sun exposure and create the ideal temperature and humidity for fruit flies. Rahinatou et al (2020) suggested that the temperature and humidity play a role in fruit fly populations, when the temperature drops (below 30°) in increasing humidity (greater than 70%), the population of C. cosyra decreases, whereas B. dorsalis increases. Meanwhile, according to Raghuvanshi et al (2012), the temperature played a specific role in regulating the behavior of the fruit fly adults, which indicates the positive correlation of prevailing temperature with the number of ovipositing females; thus, the influence of relative humidity and rainfall harmed female abundance.…”
Section: Discussionmentioning
confidence: 99%
“…During the dry season, fruits were not available, contributing to very low captures. In fact, fruit availability corresponding to months and phenology stages has an influence on the population fluctuations of fruit flies (Rahinatou et al, 2020).…”
Section: Influence Of Sites and Period Of Year On The Distribution Of...mentioning
confidence: 99%
“…The difference in abundance for the two species would be due to mango varieties within the orchards. In Mali,Rahinatou et al (2020) concluded that the preference on mango varieties were different for the two species. B. dorsalis preferred Keitt, Brooks and Smith varieties whereas C. cosyra preferred Valencia, Amelie and Davis…”
mentioning
confidence: 99%